Theory Analysis and Experiment Research of the Leg Mechanism for the Human-Carrying Walking Chair Robot. (10th December 2014) - Sang, Lingfeng; Wang, Hongbo; Wang, Shuaishuai; Chen, Na; Wen, Yuehua
Abstract : For the high carrying capacity of the human-carrying walking chair robot, in this paper, 2-UPS+UP parallel mechanism is selected as the leg mechanism; then kinematics, workspace, control, and experiment of the leg mechanism are researched in detail. Firstly, design of the whole mechanism is described and degrees of freedom of the leg mechanism are analyzed. Second, the forward position, inverse position, and velocity of leg mechanism are studied. Third, based on the kinematics analysis and the structural constraints, the reachable workspace of 2-UPS+UP parallel mechanism is solved, and then the optimal motion workspace is searched in the reachable workspace by choosing the condition number as the evaluation index. Fourth, according to the theory analysis of the parallel leg mechanism, its control system is designed and the compound position control strategy is studied. Finally, in optimal motion workspace, the compound position control strategy is verified by using circular track with the radius 100 mm; the experiment results show that the leg mechanism moves smoothly and does not tremble obviously. Theory analysis and experiment research of the single leg mechanism provide a theoretical foundation for the control of the quadruped human-carrying walking chair robot.